IDENTIFIKASI PERIBAHASA BAHASA SULA - Ridwan, Ridwan; Umar, Junaib; Fokaaya, Ramiyana (Tekstual, 2023)
This research aims to identify Sula language proverbs. Data collection was conducted using interviews, recording, and literature study, while data analysis techniques were carried out with several stages such as data reduction, data presentation, verification, and conclusion.The results found that Sula language proverbs consist of three types, namely:Â  pemeo, proverb, and parable. Pemeo means proverbs that contain advice, warnings, satire, and ridicule, such as, pia matua gu'u maka ana poa dad, ana poa maka pia matua gu'u dad moya 'Both parents can feed ten children, but ten children might not be able to feed their parents'. Proverb means a statement containing advice or teachings from the elders that is used to discourage the interlocutor, such as, nui wai mai don wag in nui maota 'Kids also know, let alone grown up ones'. Parable means a proverb that contains a comparison characterized by the use of the words, such as, like, as if, similarly, and umpama, such as fa'a gan bib lang lota baasa 'Like a goat aboard a wrecked boat'.